A composite material tube with self-lubricating properties and its preparation method and application

By using modified biochar and polymer-bound composite tubes in the slider to form a honeycomb structure to store and release lubricating oil, various problems in the traditional slider lubrication method are solved, and the self-lubricating function and high environmental adaptability of the slider are achieved.

CN119752013APending Publication Date: 2025-04-04ZHEJIANG STE PRECISION MACHINERY TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510246216.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The traditional slider lubrication method has problems such as uneven lubrication amount, blockage of oil and scale, short maintenance period, maintenance required, and large space occupation. Especially in the medical and semiconductor fields, the environmental requirements are high, and it is difficult to meet the needs of self-lubricating functions.

Method used

Using a preparation method of composite tubes, a honeycomb structure is formed by adding nanomolybdenum selenide and potassium hydroxide to the pretreated corn cob, calcining and chemically modifying, and combining with ultra-high molecular weight polyethylene and polytetrafluoroethylene to form a honeycomb structure to store and release lubricating oil.

Benefits of technology

It realizes the self-lubricating function of the slider, has the advantages of long-term maintenance-free, fuel-efficient, compact structure, low noise and environmental protection, and is suitable for areas with high environmental requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752013A_ABST
    Figure CN119752013A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lubricating materials, and specifically relates to a composite material pipe with self-lubricating properties, and a preparation method and application thereof. The preparation method comprises the following steps: a. adding nano-molybdenum selenide and potassium hydroxide to pretreated corn cobs and calcining to obtain a product; b. adding the product of step a to an ethanol aqueous solution, and then adding γ-aminopropyltriethoxysilane for heating reaction to obtain amino biochar; c. adding lauric acid, EDC and NHS to the ethanol aqueous solution, and then adding amino biochar for reaction to obtain modified biochar; d. mixing the raw materials evenly according to the weight ratio, placing them in a mold, pressing, sintering, and vacuum impregnating lubricating oil to obtain. The obtained composite material pipe has excellent wear resistance and mechanical properties, and the prepared composite material pipe can be cleverly used in transmission parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating materials, and in particular relates to a composite material pipe with self-lubricating performance and a preparation method and application thereof. Background Art

[0002] Lubrication effect is an important factor affecting the service life of transmission parts. Linear guide pairs are composed of linear guides and sliders, and play an important role in linear transmission parts. They have long operating cycles, high precision, and stable operation, so they have high requirements for lubrication performance.

[0003] The slider of the linear guide pair is usually lubricated during operation by direct supply, injection, and external oil box. Among them, the direct supply method is to install an oil nozzle at one end of the slider and supply oil to the slider through a gap lubrication pump. This method is usually used on standard sliders, even if it is used on larger sliders, it cannot be used on small sliders. In addition, if the direct supply method is in multi-point lubrication, the lubrication amount at each point will be uneven, or there will be oil stains in the lubrication pipeline after long-term use, which will block the lubrication pipe and greatly affect the stability of the equipment. The injection method is to use a syringe to inject oil into the inside of the slider through the oil filling holes at both ends of the slider. This method is usually used on micro sliders and requires regular manual refueling. The maintenance cycle is short, and the machine must be shut down for maintenance and refueling. If it is used in a module, the machine cover must be removed for refueling, which increases additional working hours and requires professional maintenance. The external oil box method is to install an oil box at both ends or one end of the slider, and lubricate the guide rail through the oil box sponge, thereby indirectly lubricating the steel balls. This type of lubrication method will take up additional space and require additional extension of the mold length, which limits the freedom of mechanical design and increases cost and complexity.

[0004] In summary, traditional slider lubrication methods all have different shortcomings. At the same time, they are even more unable to meet the requirements of medical and precision semiconductor fields with extremely high environmental requirements, because they have high requirements on the amount of grease overflowing and volatilization of guide rails and sliders. Therefore, how to solve the above problems and make the slider have self-lubricating function, so that the slider has the advantages of stable lubrication amount, long lubrication time, high production efficiency, high space utilization, environmental protection and fuel saving, is a technical problem that urgently needs to be solved.

[0005] At the same time, the existing self-lubricating composite materials mainly use materials such as molybdenum disulfide, graphite, polytetrafluoroethylene as the friction-reducing phase, which are used on bearings in a way that a lubricating film is formed through the friction surface. However, after long-term service, the above self-lubricating composite materials often have problems such as insufficient lubrication and excessive wear, which eventually lead to the failure of the sliding self-lubricating bearing. In the prior art, oil-containing microcapsules are added to the self-lubricating composite materials to increase the service life of the self-lubricating composite materials, but the mechanical properties of the self-lubricating composite materials are significantly reduced. Based on this, it is urgent to propose a composite material with excellent wear resistance and mechanical properties and self-lubricating function to meet the needs of the market. Summary of the invention

[0006] The first object of the present invention is to provide a method for preparing a composite material pipe with self-lubricating properties, which is simple and easy to practice.

[0007] A second object of the present invention is to provide a composite material pipe with self-lubricating properties, wherein the composite material pipe has excellent wear resistance and mechanical properties.

[0008] The third purpose of the present invention is to provide an application of a composite material pipe with self-lubricating properties, which has broad application prospects.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a composite material pipe with self-lubricating properties comprises the following steps: a. Adding nano-molybdenum selenide and potassium hydroxide to the pretreated corn cob and calcining to obtain a product; b. adding the product of step a to an ethanol aqueous solution, and then adding γ-aminopropyltriethoxysilane to carry out heating reaction, and obtaining the amination biochar after purification; c. adding lauric acid, EDC and NHS to the ethanol aqueous solution, and then adding the amination biochar of step b to react, and obtaining modified biochar after purification; d. According to the weight ratio, take 80-100 parts of ultra-high molecular weight polyethylene, 30-40 parts of polytetrafluoroethylene, and 8-15 parts of modified biochar in step c, mix them evenly, place them in a mold, press them, sinter them, and vacuum impregnate them with lubricating oil to obtain.

[0010] Furthermore, in step a, the mass ratio of the pretreated corn cob, nano-molybdenum selenide and potassium hydroxide is 1: (0.2-0.5): (2-5); the calcination temperature is 750-900° C., and the calcination time is 4-5 hours.

[0011] Furthermore, the method for obtaining the pretreated corn cob is as follows: according to the mass ratio of corn cob powder, sodium hydroxide solution and ferric nitrate solution being (1-2): (5-10): (1-3), the corn cob powder is added to a sodium hydroxide solution with a mass fraction of 4-6%, stirred for 4-6 hours, and then a ferric nitrate solution with a mass fraction of 6-12% is added, aged at 45-55° C. for 10-13 hours, filtered, dried, calcined at 300-400° C. for 4-6 hours, and ground to obtain the pretreated corn cob.

[0012] Furthermore, in step b, the mass ratio of the product of step a to γ-aminopropyltriethoxysilane is 1:(0.1-0.2); the temperature of the heating reaction is 50-60°C, and the heating reaction time is 4-5h; and the volume ratio of ethanol to water in the ethanol-water solution is 3:1.

[0013] Furthermore, in step c, the mass ratio of the amination biochar to lauric acid is 1:(3-8); the molar ratio of the EDC, NHS, and lauric acid is 1:1:(0.3-0.9); the reaction time is 10-15h; and the volume ratio of ethanol to water in the ethanol-water solution is 3:1.

[0014] Furthermore, the average molecular weight of the ultra-high molecular weight polyethylene in step d is 2-2.5 million.

[0015] Furthermore, the compression molding in step d is: pre-compression at 2-4 MPa, holding the pressure for 1-3 minutes, and then compression molding at 12-20 MPa.

[0016] Furthermore, during the sintering in step d, the heating rate of the sintering furnace is 8-12°C / min, the sintering furnace is heated to 250-320°C, and the insulation time is 0.5-1h.

[0017] Furthermore, in step d, the vacuum degree during vacuum impregnation of the lubricating oil is 0.05-0.1 MPa, the temperature is 80-110° C., and the impregnation time is 22-26 h.

[0018] A composite material tube with self-lubricating properties is prepared by the above-mentioned method for preparing a composite material tube with self-lubricating properties. It is a hollow tubular structure, and a plurality of honeycomb oil storage units are formed on its inner wall surface. The inner wall is elastic and can be deformed by external force to release oil from the oil storage unit.

[0019] Application of the composite material tube with self-lubricating properties in transmission components.

[0020] The beneficial technical effects of the present invention are: (1) The modified biochar of the present invention is obtained by first adding nano-molybdenum selenide and potassium hydroxide to the pretreated corn cob, then introducing amino groups on the surface of the biochar by chemical modification, and then chemically bonding the carboxyl group of lauric acid with the amino group on the surface of the biochar by coupling of EDC and NHS. The test results show that the modified biochar can improve the wear resistance and mechanical properties of the material.

[0021] (2) The present invention uses modified biochar, ultra-high molecular weight polyethylene, and polytetrafluoroethylene to prepare a composite material tube with self-lubricating properties. This is because the three materials have different temperature resistance ranges. During the sintering process, as the temperature rises, polytetrafluoroethylene and modified biochar have good retention, while the ultra-high molecular weight polyethylene will gradually become smaller and form irregular particle gaps, thereby forming a honeycomb gap on the wall of the prepared composite material tube with self-lubricating properties, thereby having the characteristics of oil storage and oil release.

[0022] (3) The present invention provides a method for preparing a composite material tube having self-lubricating properties, which is simple and easy to practice.

[0023] (4) The present invention also provides a composite material pipe with self-lubricating properties, which has excellent wear resistance and mechanical properties.

[0024] (5) The present invention applies the self-lubricating composite material tube to a transmission component after being immersed in lubricating oil for oil storage, specifically to a slider to lubricate and keep the ball in a circular track. During the cyclic motion, the ball collides with the wall of the self-lubricating composite material tube, thereby driving the lubricating oil in the honeycomb gap of the tube wall to precipitate, thereby achieving a self-lubricating effect, thereby having the following advantages: First: it can achieve long-term maintenance-free. Ordinary non-self-lubricating products need to add lubricating oil once every 10-100 kilometers to keep the ball and the contact surface lubricated. The slide rail of the composite tube with built-in self-lubricating properties of the present invention can be maintenance-free for 20,000 kilometers, which greatly reduces the cost of continuous downtime and maintenance. Second: It is more fuel-efficient. The lubricating oil in the composite tube with self-lubricating properties only supplies the amount required to maintain the lubrication performance of the ball. Even if it runs for a long time, the consumption of lubricating oil is very small. Therefore, the lubrication performance can be maintained for a long time. Third: The structure is more compact and space-saving. Compared with the external lubricating component type product, the composite tube with self-lubricating properties does not need to be lengthened, is not restricted by the installation space or stroke length, and can be easily used to replace the old product. Fourth: The noise is lower, because the honeycomb gap of the tube wall of the composite tube with self-lubricating properties is filled with lubricating oil, and when the ball collides with the tube wall, it has a good vibration reduction and noise reduction effect. Fifth: It is more suitable for use in laboratories, medical treatment, semiconductor industry and other fields with high environmental requirements, because of its special storage and oil release characteristics, that is, the lubricating oil is evenly stored in the honeycomb gaps inside the tube wall, so there will be no large-scale overflow of lubricating oil, and the working environment will not be polluted by the overflow of lubricating oil. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the product obtained in step d of Example 1 of the present invention before and after oil immersion; wherein Figure 1 (a) is a schematic diagram of the product obtained in step d of Example 1 before oil immersion; Figure 1 (b) is a schematic diagram of the product obtained in step d of Example 1 after being immersed in oil; Figure 2 It is a schematic diagram of the enlarged structure of the inner wall of the composite material tube with self-lubricating properties of the present invention; Figure 3 It is a schematic diagram of the three-dimensional structure of the slider; Figure 4 It is a schematic diagram of the slider structure; Figure 5 Schematic diagram of the lubricating oil precipitation state after the ball collides with the inside of the composite tube; Reference numerals: 1. return device; 2. ball circulation retaining device; 3. limiting roller; 5. composite material tube. DETAILED DESCRIPTION

[0026] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0027] The average molecular weight of the ultra-high molecular weight polyethylene of the present invention is 2-2.5 million.

[0028] 1. Implementation Example 1 A method for preparing a composite material tube with self-lubricating properties, the specific preparation process is as follows: a. According to the mass ratio of corn cob powder, sodium hydroxide solution and ferric nitrate solution of 1.5:8:2, corn cob powder was added to 5% sodium hydroxide solution, stirred for 5 hours, and then 9% ferric nitrate solution was added, aged at 50°C for 11 hours, filtered and dried, and then calcined at 350°C for 5 hours, and the pretreated corn cob was obtained after grinding; according to the mass ratio of pretreated corn cob, nano-molybdenum selenide and potassium hydroxide of 1:0.4:3, nano-molybdenum selenide and potassium hydroxide were added to the pretreated corn cob, and the product was calcined at 800°C for 4.5 hours; b. According to the mass ratio of the product of step a to γ-aminopropyltriethoxysilane of 1:0.15, the product of step a is added to an ethanol aqueous solution (v / v=3:1), and then γ-aminopropyltriethoxysilane is added, and the mixture is heated at 55°C for 4.5h to react, and the amination biochar is obtained by filtering, washing and drying; c. Add lauric acid and EDC to an ethanol aqueous solution (v / v=3:1) at a mass ratio of 1:6 for amination biochar and lauric acid and a molar ratio of 1:1:0.5 for EDC and NHS lauric acid, stir for 12 minutes, then add NHS, and then add the amination biochar in step b, react at room temperature for 12 hours, centrifuge, wash, and dry to obtain modified biochar; d. According to the weight ratio, take 90 parts of ultra-high molecular weight polyethylene, 35 parts of polytetrafluoroethylene, and 10 parts of modified biochar in step c, mix them evenly and place them in a mold, first pre-press them at 3 MPa, hold the pressure for 2 minutes, and then press them at 15 MPa; then place the molded product containing the mold in a sintering furnace, heat the sintering furnace to 260°C at a rate of 10°C / min, keep it warm for 0.6h, cool it to room temperature and demold it, place the demolded product in a vacuum drying oven with a vacuum degree of 0.08MPa and filled with lubricating oil, and immerse it at 90°C for 24h.

[0029] A composite material tube with self-lubricating properties is prepared by the above preparation method. The product of the present invention is a hollow tubular structure, the thickness of the tube wall is 0.3-0.8 mm, and the inner wall surface is formed with a plurality of honeycomb-shaped gaps, namely the oil storage unit 8, the size of the oil storage unit 8 is 4-20 μm, and its unique gap structure has a good oil storage function after oil immersion. The inner wall is elastic, and the deformation can be generated by external force extrusion to make the oil storage unit 8 release oil. The schematic diagram before and after oil immersion is shown in FIG. Figure 1 As shown, Figure 1 (a) is a schematic diagram of the product obtained in step d of Example 1 before oil immersion; Figure 1 (b) is a schematic diagram of the product obtained in step d of Example 1 after being immersed in oil.

[0030] Example 2 A method for preparing a composite material tube with self-lubricating properties, the specific preparation process is as follows: a. According to the mass ratio of corn cob powder, sodium hydroxide solution and ferric nitrate solution of 2:10:3, corn cob powder was added to a 6% sodium hydroxide solution, stirred for 6 hours, and then a 12% ferric nitrate solution was added, aged at 55°C for 10 hours, filtered and dried, and then calcined at 400°C for 4 hours, and the pretreated corn cob was obtained after grinding; according to the mass ratio of pretreated corn cob, nano-molybdenum selenide and potassium hydroxide of 1:0.5:5, nano-molybdenum selenide and potassium hydroxide were added to the pretreated corn cob, and the product was calcined at 900°C for 4 hours; b. According to the mass ratio of the product of step a to γ-aminopropyltriethoxysilane of 1:0.2, the product of step a is added to an ethanol aqueous solution (v / v=3:1), and then γ-aminopropyltriethoxysilane is added, and the mixture is heated at 60°C for 4 hours, and then filtered, washed and dried to obtain amino biochar; c. Add lauric acid and EDC to an ethanol aqueous solution (v / v=3:1) at a mass ratio of 1:8 for amination biochar and lauric acid and a molar ratio of 1:1:0.9 for EDC and NHS lauric acid, stir for 12 minutes, then add NHS, and then add the amination biochar in step b, react at room temperature for 15 hours, centrifuge, wash, and dry to obtain modified biochar; d. According to the weight ratio, take 100 parts of ultra-high molecular weight polyethylene, 40 parts of polytetrafluoroethylene, and 15 parts of modified biochar in step c, mix them evenly and place them in a mold, first pre-press them at 4 MPa, hold the pressure for 1 minute, and then press them at 20 MPa; then place the molded product containing the mold in a sintering furnace, heat the sintering furnace to 320°C at a rate of 12°C / min, keep it warm for 0.5h, cool it to room temperature and demold it, place the demolded product in a vacuum drying oven with a vacuum degree of 0.1MPa and filled with lubricating oil, and immerse it at 110°C for 22h.

[0031] A composite material pipe with self-lubricating performance is prepared by adopting the preparation method.

[0032] Example 3 A method for preparing a composite material tube with self-lubricating properties, the specific preparation process is as follows: a. According to the mass ratio of corn cob powder, sodium hydroxide solution and ferric nitrate solution of 1:5:1, corn cob powder was added to a 4% sodium hydroxide solution, stirred for 4 hours, and then a 6% ferric nitrate solution was added, aged at 45°C for 13 hours, filtered, dried, and then calcined at 300°C for 6 hours, and the pretreated corn cob was obtained after grinding; according to the mass ratio of pretreated corn cob, nano-molybdenum selenide and potassium hydroxide of 1:0.2:2, nano-molybdenum selenide and potassium hydroxide were added to the pretreated corn cob, and the product was calcined at 750°C for 5 hours; b. According to the mass ratio of the product of step a to γ-aminopropyltriethoxysilane of 1:0.1, the product of step a is added to an ethanol aqueous solution (v / v=3:1), and then γ-aminopropyltriethoxysilane is added, and the mixture is heated at 50°C for 5 hours, and then filtered, washed and dried to obtain amino biochar; c. Add lauric acid and EDC to an ethanol aqueous solution (v / v=3:1) at a mass ratio of aminated biochar to lauric acid of 1:3 and a molar ratio of EDC to NHS lauric acid of 1:1:0.3. Stir for 12 minutes and then add NHS. Then add the aminated biochar from step b. React at room temperature for 10 hours. Centrifuge, wash and dry to obtain modified biochar. d. According to the weight ratio, take 80 parts of ultra-high molecular weight polyethylene, 30 parts of polytetrafluoroethylene, and 8 parts of modified biochar in step c, mix them evenly and place them in a mold, first pre-press them at 2 MPa, hold the pressure for 3 minutes, and then press them at 12 MPa; then place the molded object containing the mold in a sintering furnace, heat the sintering furnace to 250°C at a rate of 8°C / min, keep it warm for 1 hour, cool it to room temperature and demold it, place the demolded product in a vacuum drying oven with a vacuum degree of 0.05 MPa and filled with lubricating oil, and immerse it at 80°C for 26 hours.

[0033] A composite material pipe with self-lubricating performance is prepared by adopting the preparation method.

[0034] (II) Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that molybdenum disulfide is used instead of modified biochar, and the other preparation conditions are the same as Example 1.

[0035] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step a is omitted, and in step b, pretreated corn cobs are used instead of the product of step a for subsequent preparation, and the preparation conditions are the same as those of Example 1.

[0036] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that step b is omitted, and in step c, the product of step a is used to replace the amination biochar of step b for subsequent preparation, and the preparation conditions are the same as those of Example 1.

[0037] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that steps a and b are omitted, and in step c, pretreated corn cobs are used instead of the amination biochar in step b for subsequent preparation, and the preparation conditions are the same as in Example 1.

[0038] (III) Test examples The properties of the materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested, and the detection indicators and methods were as follows: (1) Friction performance According to GB / T 12444-2006, the friction performance between each group of materials and the friction pair (45# steel) was measured using a test ring-test block wear test device under the conditions of 2.24m / s and 66N. The results are shown in Table 1.

[0039] (2) Compression strength According to GB / T 1041-2008, the compression performance of each group was characterized using a dynamic thermomechanical analysis tester (specimen size 10mm×10mm×4mm). The results are shown in Table 1.

[0040] (3) Flexural modulus According to GB / T 9341-2008, the compression performance of each group was characterized using a dynamic thermomechanical analysis tester (specimen size 80mm×10mm×4mm). The results are shown in Table 1.

[0041] Table 1 It can be seen from Table 1 that, compared with Examples 1-3, the wear resistance and mechanical properties of the material obtained by using molybdenum disulfide instead of modified biochar in Comparative Example 1 are reduced, and the wear resistance and mechanical properties of the material obtained by adjusting the modified biochar preparation process in Comparative Examples 2-4 are significantly reduced. Analysis shows that the present invention uses potassium hydroxide as an activator, and by adding nano-molybdenum selenide to the pretreated corn cob, the porosity of biochar is increased, the adsorption performance and catalytic activity of biochar are improved, and then amino groups are introduced on the surface of biochar through chemical modification to change the surface properties of biochar, and increase its reactivity with other substances; then, under the coupling action of EDC and NHS, the carboxyl group of lauric acid is chemically bonded to the amino group on the surface of the amino-modified biochar, and this chemical bonding forms a transfer film during the friction process, thereby enhancing the wear resistance and mechanical properties of the biochar.

[0042] (IV) Application examples The self-lubricating composite material tube prepared in Example 1 can be used in transmission components, specifically placed in the slider of the ball linear guide pair. The ball linear guide pair is a conventional component in the field, which includes a linear guide, a slider and a return device 1 respectively fixed at both ends of the slider. The slider can move linearly along the guide rail. The slider slides between the slider and the slide rail through the ball. The balls in the slider circulate and roll in a circulation channel. The circulation channel is composed of a ball circulation retaining device 2, a limiting roller 3 corresponding to the ball circulation retaining device 2, and two return devices 1. The ball circulation retaining device 2 can limit the circulation of the balls. The rolling position is to prevent the balls from colliding with each other or falling off. An arc-shaped roller is provided between the ball circulation retaining device 2 and the limiting roller 3 to assist the balls in turning. A turning roller is formed between the arc-shaped roller and the return device 1, so that the balls can circulate infinitely in the circulation channel. The present invention ingeniously installs the prepared composite material tube 5 with self-lubricating properties in the limiting roller 3. The balls circulate in the circulation channel. When they move to the limiting roller 3, they collide with the inner wall of the composite material tube 5 soaked in lubricating oil, so that the lubricating oil stored in the oil storage unit 8 is squeezed by external force and precipitated, thereby achieving the purpose of self-lubrication. Its effect is as follows Figure 5 shown.

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A method for preparing a composite material tube with self-lubricating properties, characterized in that: The following steps are involved: a. Adding nano-molybdenum selenide and potassium hydroxide to the pretreated corn cob and calcining to obtain a product; b. adding the product of step a to an ethanol aqueous solution, and then adding γ-aminopropyltriethoxysilane to carry out heating reaction, and obtaining the amination biochar after purification; c. adding lauric acid, EDC and NHS to the ethanol aqueous solution, and then adding the amination biochar of step b to react, and obtaining modified biochar after purification; d. According to the weight ratio, take 80-100 parts of ultra-high molecular weight polyethylene, 30-40 parts of polytetrafluoroethylene, and 8-15 parts of modified biochar in step c, mix them evenly, place them in a mold, press them, sinter them, and vacuum impregnate them with lubricating oil to obtain.

2. The method for preparing a composite material tube having self-lubricating properties according to claim 1, characterized in that: The mass ratio of the pretreated corn cob, nano-molybdenum selenide and potassium hydroxide in step a is 1: (0.2-0.5): (2-5); the calcination temperature is 750-900° C. and the calcination time is 4-5 hours.

3. The method for preparing a composite material tube having self-lubricating properties as claimed in claim 2, characterized in that: The method for obtaining the pretreated corn cob is as follows: according to the mass ratio of corn cob powder, sodium hydroxide solution and ferric nitrate solution being (1-2): (5-10): (1-3), the corn cob powder is added to a sodium hydroxide solution with a mass fraction of 4-6%, stirred for 4-6 hours, and then a ferric nitrate solution with a mass fraction of 6-12% is added, aged at 45-55° C. for 10-13 hours, filtered, dried, calcined at 300-400° C. for 4-6 hours, and ground to obtain the pretreated corn cob.

4. The method for preparing a composite material tube having self-lubricating properties as claimed in claim 1, characterized in that: In step b, the mass ratio of the product of step a to γ-aminopropyltriethoxysilane is 1:(0.1-0.2); the temperature of the heating reaction is 50-60° C., and the heating reaction time is 4-5 hours; and the volume ratio of ethanol to water in the ethanol-water solution is 3:

1.

5. The method for preparing a composite material pipe having self-lubricating properties as claimed in claim 1, characterized in that: In step c, the mass ratio of the aminated biochar to lauric acid is 1:(3-8); the molar ratio of the EDC, NHS, and lauric acid is 1:1:(0.3-0.9); the reaction time is 10-15 hours; and the volume ratio of ethanol to water in the ethanol-water solution is 3:

1.

6. The method for preparing a composite material tube having self-lubricating properties as claimed in claim 1, characterized in that: The compression molding in step d is: pre-compression at 2-4 MPa, holding the pressure for 1-3 minutes, and then compression molding at 12-20 MPa.

7. The method for preparing a composite material tube having self-lubricating properties as claimed in claim 1, characterized in that: During the sintering in step d, the heating rate of the sintering furnace is 8-12°C / min, the sintering furnace is heated to 250-320°C, and the insulation time is 0.5-1h.

8. The method for preparing a composite material tube having self-lubricating properties as claimed in claim 1, characterized in that: During the vacuum impregnation of the lubricating oil in step d, the vacuum degree is 0.05-0.1 MPa, the temperature is 80-110° C., and the impregnation time is 22-26 h.

9. A composite material tube with self-lubricating properties, characterized in that: The composite material tube with self-lubricating properties is prepared by the preparation method of any one of claims 1 to 8. It is a hollow tubular structure, and a plurality of honeycomb oil storage units are formed on the inner wall surface. The inner wall is elastic and can be deformed by external force to release oil from the oil storage unit.

10. Use of the composite material tube with self-lubricating properties as claimed in claim 9 in transmission parts.

Citation Information

Patent Citations

  • High temperature wear-resisting self-lubricating composite material added with MoSe2 and preparation method of composite material

    CN102864395A

  • Self-repairing self-lubricating material and preparation method thereof

    CN108395657A

  • Preparation of carbon-modified molybdenum diselenide nanometer lubricating material and application of carbon-modified molybdenum diselenide nanometer lubricating material to iron-based nanometer composite coating process

    CN111994882A

  • LUBRICANT COMPOSITION BASED ON METALLIC NANOPARTICLES

    FR3004723A1

  • Compositions and methods relating to tribology

    US20060089270A1